Intrinsic apoptotic pathway and G2/M cell cycle arrest involved in tubeimoside I-induced EC109 cell death - Xu, Yang; Wang, Guanghui; Chen, Quancheng; Lin, Ting; Zeng, Zhiping; Luo, Qiang; Liu, Jie; Sun, Cuiling (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Objective: Squamous esophageal carcinoma is highly prevalent in developing countries, especially in China. Tu Bei Mu (TBM), a traditional folk medicine, has been used to treat esophageal squamous cell carcinoma (ESCC) for a long term. tubeimoside I (TBMS1) is the main component of TBM, exhibiting great anticancer potential. In this study, we investigated the mechanism of TBMS1 cytotoxic effect on EC109 cells. Methods: Comparative nuclear proteomic approach was applied in the current study and we identified several altered protein spots. Further biochemical studies were carried out to detect the mitochondrial membrane potential, cell cycle and corresponding proteins’ expression and location. Results: Subcellular proteomic study in the nucleus from EC109 cells revealed that altered proteins were associated with mitochondrial function and cell proliferation. Further biochemical studies showed that TBMS1-induced molecular events were related to mitochondria-induced intrinsic apoptosis and P21-cyclin B1/cdc2 complex-related G2/M cell cycle arrest. Conclusions: Considering the conventional application of TBM in esophageal cancer, TBMS1 therefore may have a great potential as a chemotherapeutic drug candidate for ESCC.